Molecular double core hole electron spectroscopy for chemical analysis - Tashiro, Motomichi; Ehara, Masahiro; Fukuzawa, Hironobu; Ueda, Kiyoshi; Buth, Christian; Kryzhevoi, Nikolai V.; Cederbaum, Lorenz S. (The journal of chemical physics, 2010)
We explore the potential of double core hole electron spectroscopy for chemical analysis in terms of x-ray two-photon photoelectron spectroscopy. The creation of deep single and double core vacancies induces significant reorganization of valence electrons. The corresponding relaxation energies and the interatomic relaxation energies are evaluated by complete active space self-consistent field (CASSCF) calculations. We propose a method on how to experimentally extract these quantities by the measurement of single ionization potentials (IPs) and double core hole ionization potentials (DIPs). The influence of the chemical environment on these DIPs is also discussed for states with two holes at the same atomic site and states with two holes at two different atomic sites. Electron density difference between the ground and double core hole states clearly shows the relaxations accompanying the double core hole ionization. The effect is also compared to the sensitivity of single core hole IPs arising in single core hole electron spectroscopy. We have demonstrated the method for a representative set of small molecules LiF, BeO, BF, CO, N2, C2H2, C2H4, C2H6, CO2, and N2O. The scalar relativistic effect on IPs and on DIPs are briefly addressed.
Gesehen am 15.09.2023